Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1063/1.1784544
|View full text |Cite
|
Sign up to set email alerts
|

Band-gap modified Al-doped Zn1−xMgxO transparent conducting films deposited by pulsed laser deposition

Abstract: Al-doped Zn1−xMgxO films have been deposited on glass substrates at a substrate temperature of 200°C by a pulsed laser deposition system. A resistivity of 3×10−4Ωcm was obtained at x=0.06. Film resistivity was found to increase with further increases in Mg composition. The maximum band gap of films with a resistivity ρ⩽1×10−3Ωcm was found to be 3.97eV, demonstrating band-gap engineering possibilities in the range of Eg=3.5–3.97eV with a resistivity ρ⩽1×10−3Ωcm. The average transmittance of the films was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 12 publications
9
87
1
Order By: Relevance
“…As can be seen from the inset, the mobilities are reduced considerably with the change of Mg content. It can be also found that the simulation results agree very well with the reported experiment data, [16][17][18] 167 O, respectively and the electron drift velocity reaches steady state quickly with inappreciable velocity overshoot below 1000 kV/cm. In contrast, for the electric field strength in excess of 1000 kV/cm, a significant overshoot can be observed clearly for both materials.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…As can be seen from the inset, the mobilities are reduced considerably with the change of Mg content. It can be also found that the simulation results agree very well with the reported experiment data, [16][17][18] 167 O, respectively and the electron drift velocity reaches steady state quickly with inappreciable velocity overshoot below 1000 kV/cm. In contrast, for the electric field strength in excess of 1000 kV/cm, a significant overshoot can be observed clearly for both materials.…”
Section: Resultssupporting
confidence: 79%
“…Up to date, only limited studies have been reported on the steady-state electron transport properties of Zn 1−x Mg x O. Experimental measurements of the low-field mobility of this material were performed by D. J. Cohen, 16 K. Matsubara 17 and Yi Ke 18 since Ohtomo 19 firstly prepared the Zn 1−x Mg x O films in 1998. In theory, Z. Yarar 20 reported the steady-state electron transport characteristics of Zn 1−x Mg x O using the Monte Carlo simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The latter could be caused by a decreased incorporation of Al in the mixed Zn 1−x Mg x O lattice or changes in the dopant energy level and an identification of the particular mechanism was not feasible so far. 13,15 As our analysis clearly shows, the Al content, within the error of the measurement, is not affected by the large quantities of Mg in the lattice (Fig. 1b).…”
mentioning
confidence: 68%
“…Previous studies have shown that Zn 1−x Mg x O up to x=0.3 can be doped with Al, though not as efficiently as plain ZnO. [13][14][15] Compared to ZnO:Al a significant reduction in conductivity was observed and related to a decrease in carrier concentration and electron mobility in the disordered lattice. 13,14 Within this study the system was further investigated and electrical properties were correlated to optical and crystal structure properties, as well as composition analysis with XPS.…”
Section: 9-11mentioning
confidence: 99%
“…33 In addition, the incorporation of magnesium in the Mg x Zn 1−x O film introduces an alloy scattering mechanism, which decreases the electron mobility. 14 The carrier concentration is also decreased with increasing magnesium concentration, which indicates that the addition of magnesium can lower the Ga doping efficiency.…”
Section: Electrical Properties Of Ga-doped Mg X Zn 1−x O Thin Filmsmentioning
confidence: 86%